2019
DOI: 10.1101/513747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The antimicrobial peptide Defensin cooperates with Tumour Necrosis Factor to drive tumour cell death in Drosophila

Abstract: 23Antimicrobial peptides (AMPs) are small cationic molecules best known as 24 mediators of the innate defence against microbial infection. While in vitro and 25 ex vivo evidence suggest AMPs' capacity to kill cancer cells, in vivo 26 demonstration of an anti-tumour role of endogenous AMPs is lacking. Using a 27Drosophila model of tumourigenesis, we reveal a role for the AMP Defensin in 28 the control of tumour progression. Our results reveal that Tumour Necrosis 29Factor mediates exposure of phosphatidylserine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 60 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…In this context, our study demonstrates that naturally occurring bacterial infection can promote tumor regression in two drosophila tumor models, and it supports the idea that infection-dependent production of diptericin and drosomycin, two antimicrobial peptides, may be key drivers of this regression through increased tumor cell death. Our results are supported by previous studies showing that increase in Toll and Imd signaling in tissues distant from the tumor result in increased tumor cell death in dlg mutant animals [37][38][39] . Imd and Toll pathways could act synergistically to produce AMP, as already reported elsewhere 40 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this context, our study demonstrates that naturally occurring bacterial infection can promote tumor regression in two drosophila tumor models, and it supports the idea that infection-dependent production of diptericin and drosomycin, two antimicrobial peptides, may be key drivers of this regression through increased tumor cell death. Our results are supported by previous studies showing that increase in Toll and Imd signaling in tissues distant from the tumor result in increased tumor cell death in dlg mutant animals [37][38][39] . Imd and Toll pathways could act synergistically to produce AMP, as already reported elsewhere 40 .…”
Section: Discussionsupporting
confidence: 91%
“…However, the striking rise in immunotherapeutic strategies over the few past decades, exemplified by the attribution of the 2018 Nobel Prize in Medicine, calls for a re-evaluation of mechanisms linking infections and spontaneous tumor regression. While studies have mainly focused on adaptive immunity for the elaboration of new drugs 47 , our study, together with other recent studies in flies 38,39 , has revealed some molecular aspects mediating the forgotten potential of the innate immune system in the control of tumor burden. Further efforts should be made to elucidate the precise molecular mechanisms leading to cancer regression in response to innate immune system activation: this may also help with the design of new therapeutic strategies using drugs that mimic the effect of infections to establish an innate immune profile adverse to cancer cells.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Their expression is induced to very high levels upon challenge to provide microbicidal concentrations in the μM range. Numerous studies have revealed unique roles that AMPs may play in host physiology including anti-tumor activity (Suttmann et al, 2008; Kuroda et al, 2015; Araki et al, 2018; Parvy et al, 2019), inflammation in aging (Cao et al, 2013; Kounatidis et al, 2017; E et al, 2018), involvement in memory (Bozler et al, 2017; Barajas-Azpeleta et al, 2018), mammalian immune signaling (van Wetering et al, 2002; Tjabringa et al, 2003), wound-healing (Tokumaru et al, 2005; Chung et al, 2017), regulation of the host microbiota (Login et al, 2011; Mergaert et al, 2017), tolerance to oxidative stress (Zhao et al, 2011; Zheng et al, 2007), and of course microbicidal activity (Imler and Bulet, 2005; Wimley, 2010). The fact that AMP genes are immune inducible and expressed at high levels has led to the common assumption they play a vital role in the innate immune response.…”
Section: Introductionmentioning
confidence: 99%